Multiple Electrode Aggregometry is an adequate method for aspirin response testing in myeloproliferative neoplasms and differentiates the mechanisms of aspirin resistance. Issue 142 (June 2016) - Gillet, Benjamin; Ianotto, Jean-Christophe; Mingant, Fanny; Didier, Romain; Gilard, Martine; Ugo, Valérie; Lippert, Eric; Galinat, Hubert
Abstract: Introduction: In myeloproliferative neoplasms (MPN), aspirin reduces the thrombotic risk. Nevertheless, aspirin resistance may be due to excessive platelet production ("turnover" resistance). Aspirin resistance can also result from a lack of effect of aspirin; this second component is called "intrinsic resistance". Two biological tests are considered reference methods for the assessment of aspirin resistance: TXB2 assay and Light Transmittance Aggregometry (LTA) with arachidonic acid. Materials & methods: We have compared a third method, the Multiple Electrode Aggregometry (MEA), performed with arachidonic acid on the Multiplate® analyzer, with both reference methods. Thirty-six patients with MPN were assessed for aspirin resistance with all three techniques. 30 patients devoid of MPN were used as controls. Results: The three methods were statistically equivalent: LTA and TXB2 were comparable methods (ROC curve AUC = 0.844 > 0.7; LTA cutoff = 67%). At this threshold, LTA had a sensitivity of 73% and a specificity of 96%. MEA (without added aspirin) and TXB2 were also comparable (ROC curve AUC = 0.782; MEA cutoff = 31 U), but at this threshold, 11 patients (30%) were falsely positive with MEA. Last, MEA and LTA were comparable (ROC curve AUC = 0.888; MEA cutoff = 56 U), with a sensitivity of 90% and a specificity of 84.6%. Besides, MEA gave an insight into the mechanism of aspirin resistance (turnover and/or intrinsic). Conclusion: MEA is both rapid and reliable as compared to reference methods. Clinical correlation with risk of re-thrombosis should definitively validate this method and the best cutoff value. Highlights: MEA is comparable to reference methods for aspirin resistance assessment. MEA distinguishes turnover versus intrinsic resistance. Turnover resistance is predominant in patients with myeloproliferative neoplasms.